Profil Vo2max Atlet Beladiri Gorontalo Persiapan Pon Aceh-Sumut 2024 - Datau, Suriyadi; Ilham, Al (Universitas Negeri Gorontalo, 2024)
Cardiovascular endurance is an important component in the performance of martial arts athletes, especially in facing high and continuous physical intensity demands. One of the main indicators in assessing cardiovascular endurance capacity is VO₂Max, which is the maximum volume of oxygen that the body can consume per unit time during maximum physical activity. VO₂Max is crucial in martial arts that require endurance and speed over a long period of time. This study aims to examine the VO₂Max profile in Gorontalo martial arts athletes participating in the 2024 Aceh-North Sumatra National Sports Week (PON). The study was conducted through a descriptive quantitative approach using the Multistage Fitness Test (MFT) method to measure athletes' VO₂Max. Data were obtained from 9 Gorontalo martial arts athletes representing various sports, such as taekwondo, karate, wushu, muaythai, and kick boxing. The measurement results showed that the average VO₂Max of athletes was 41.31 ml/kg/minute with a standard deviation of 5.26, which was spread in the categories of